Fetal intra-abdominal umbilical vein varix in monochorionic twin: is it significant? - Ismail, Hamizah; Chang, Yao-Lung; Chang, Shuenn-Dyh; Nusee, Zalina (Universiti Sains Malaysia, 2012)
A 30 year old Taiwanese in her second pregnancy conceived spontaneously to a monochorionic twin pregnancy. A routine ultrasound surveillance at 27 weeks of gestation revealed a selective intrauterine growth restriction (sIUGR) fetus and an appropriate gestational age (AGA) fetus. The AGA fetus was found to have fetal intra-abdominal umbilical vein (FIUV) varix. Serials ultrasound showed no changes in the FIUV varix. Two weeks later the pregnancy progressed to twin-twin transfusion syndrome (TTTS). Repeated amnioreductions were required at 29 and 30 weeks gestation. Pregnancy ends up with Caesarean section at 31 weeks due to fetal distress in the sIUGR fetus. Both fetuses survived the neonatal period with problems of prematurity. The FIUV varix disappeared few days following delivery